2022
DOI: 10.1039/d2ce00825d
|View full text |Cite
|
Sign up to set email alerts
|

Metal oxide charge transporting layers for stable high-performance perovskite solar cells

Abstract: Charge transporting layers (CTLs) are essential components of perovskite solar cells (PSCs) that significantly impact their performance and stability. Metal oxide CTLs are extensively used for PSCs owing to their...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 250 publications
0
3
0
Order By: Relevance
“…With the sustainable development of the social economy, excessive energy consumption has always been an important issue. [1][2][3][4][5][6][7] Previous reports have shown that about 22% of the electric power in the USA is consumed in the field of lighting. 8 Thus, how to reduce lighting energy consumption has become the research direction of many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…With the sustainable development of the social economy, excessive energy consumption has always been an important issue. [1][2][3][4][5][6][7] Previous reports have shown that about 22% of the electric power in the USA is consumed in the field of lighting. 8 Thus, how to reduce lighting energy consumption has become the research direction of many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, TiO 2 is the most used in perovskite solar cells, due to developments inherited from research on dye-sensitized solar cells (DSSCs) [29]. However, TiO 2 has slow electron mobility (about 0.1-4 cm 2 V −1 s −1 ), requires high-temperature processing (annealing temperatures at 400-450 • C), and has strong photocatalytic activity in the ultraviolet region, which impacts device performance and stability [21,30]. Thus, TiO 2 needs to be replaced by another, more suitable n-type metal oxide layer as an ETL to allow further development for commercial applications [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Charge transport layers (CTLs) based on organic materials (such as PPEDOT: PSS, P3HT, and spiro-OMeTAD) offer low-temperature solution-based deposition and greater mechanical strength; however, their use is limited because of chemical instability, low charge carrier mobility, and high production cost . On the contrary, state-of-the-art, low-cost, and controlled synthesis having desired thin film morphology, high charge carrier mobility and chemical stability, and tunable optoelectronic traits makes inorganic metal oxides standout CTL materials . Using metal oxide semiconductors as CTLs (both as ETLs and HTLs) has been proven very effective, not only in PCE and stability enhancement but also in preventing perovskite material decomposition, specifically at the interface. In our device design, comparative to ZnO and SnO 2 as ETLs and CuO and Cu 2 O as HTLs, we found that TiO 2 as an ETL and NiO both assist in achieving 31.09% power conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%